2009
DOI: 10.1002/lt.21782
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 is a key mediator of murine steatotic liver warm ischemia/reperfusion injury

Abstract: Steatotic donors are routinely rejected for transplantation because of their increased rate of primary nonfunction. These grafts are more sensitive to ischemia/reperfusion (I/R) during transplantation. Removal of endotoxin before reperfusion improves liver performance post-I/R. We hypothesize that the main modality of injury in steatotic livers is toll-like receptor 4 (TLR4) signaling. We fed 4-week-old control and TLR4-deficient (TLR4KO) mice a normal diet (ND) or a 60% high-fat diet (HFD) for 4 weeks to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 41 publications
6
44
1
2
Order By: Relevance
“…Indeed, the results in IL-6 2/2 mice demonstrated the regulatory role of this cytokine in the Treg/Th17 balance during antidonor immune response. High amounts of IL-6 are released in response to the surgical procedure, after TLR activation in the context of bacterial contamination and/or ischemiareperfusion injury (29,(46)(47)(48)(49). IL-6 can also be produced by dendritic cells in an Ag-specific manner through a dendritic/T cell cross-talk via the CD40-CD154 interactions (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the results in IL-6 2/2 mice demonstrated the regulatory role of this cytokine in the Treg/Th17 balance during antidonor immune response. High amounts of IL-6 are released in response to the surgical procedure, after TLR activation in the context of bacterial contamination and/or ischemiareperfusion injury (29,(46)(47)(48)(49). IL-6 can also be produced by dendritic cells in an Ag-specific manner through a dendritic/T cell cross-talk via the CD40-CD154 interactions (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were euthanized by isoflurane asphyxiation and cervical dislocation at 1, 3, and 18 hours after LPS exposure, and kidneys and serum were collected for molecular analysis. For experiments using TLR4-deficient animals, TLR4 knockout (TLR4KO) mice were generated by crossing C57BL/10ScN mice with the tlr4 LPS-d mutation onto the C57BL/6 background for at least five generations (Ellett et al, 2009). All studies were conducted in accordance with the recommendations in the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
“…249 An investigation of the relevance of other TLR family members to stroke indicated that the expression of TLR7 and TLR8 were associated with poor outcome and enhanced inflammation in acute ischemic stroke 252 but that mice carrying a TLR3 or TLR9 ablation exhibited comparable brain damage after cerebral I/R injury with WT controls. 253 As in stroke insults, posthepatic ischemia, the chronic pharmacological or genetic inhibition of TLR4 accounts for the improved survival and decreased liver pathology via suppression of the inflammatory response, 254 apoptosis, 255 oxidative stress, 256 and endothelial overactivation. 257 The TLR2 mRNA level was increased in the ischemic lobes of mice that underwent partial hepatic I/R, and this increase was associated with an increase in TNF-α expression but was reversely accompanied with the alleviation of liver damage.…”
Section: Upstream Irf Signaling In I/r Injurymentioning
confidence: 99%